Carlos Barciela López, M. Inmaculada López Ortiz y Joaquín Melgarejo Moreno (Eds). Los bienes culturales y su aportación al desarrollo sostenible. Alicante, Publicaciones de la Universidad de Alicante, 2012, 623 págs., ISBN: 978-84-9717-216-5. - Roca Rosell, Antoni (Investigaciones de Historia Económica, 2019)
Sin resumen